(untitled) (Research, Society and Development, 2021)
The population’s knowledge of skin cancer can be decisive for its clinical outcome since the poor prognosis is related to the progress of the disease. The objective of the study was to verify the knowledge in this university environment about the characteristics and care in the prevention of skin cancer. This is a cross-sectional study carried out in Maringá-PR, using a validated questionnaire. 458 people were interviewed, most of whom were women (62.01%), ranging from students in the exact, human, or biological fields and professionals at the institution. For analysis, the interviewees’ skin phototype, and family income were considered. The methodology was based on a score made by scoring the questions, separating the interviewees into groups with low and high knowledge. The captured data show that most of the associates had good knowledge related to the disease, which was positively related to the study area of the participants - health, and family income - above 6 referenced. However, impending preventive practices are not widespread, even in groups with good knowledge. Therefore, this work shows the need for informational actions on skin neoplasms and their practice by the population, in order to help in the prevention and early detection of the disease.